1987
DOI: 10.1002/mus.880100612
|View full text |Cite
|
Sign up to set email alerts
|

Hypogravity‐induced atrophy of rat soleus and extensor digitorum longus muscles

Abstract: Prolonged exposure of humans to hypogravity causes weakening of their skeletal muscles. This problem was studied in rats exposed to hypogravity for 7 days aboard Spacelab 3. Hindlimb muscles were harvested 12-16 hours postflight for histochemical, biochemical, and ultrastructural analyses. The majority of the soleus and extensor digitorum longus fibers exhibited simple cell shrinkage. However, approximately 1% of the fibers in flight soleus muscles appeared necrotic. Flight muscle fibers showed increased glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 18 publications
4
46
0
Order By: Relevance
“…Elevated Ca 2ϩ activates calcium-activated proteases, calpains, which partially degrade myofibrillar proteins and ryanodine receptors, leading to breakdown of myofibrils and enhanced calcium efflux (11,27,31). Calcium-activated protease activity increases in atrophying soleus muscles during HSU (12,33) and spaceflight (28) and directly parallels the development of CCLs in tenotomy (5). Immobilized soleus muscles show significant increases in total calcium concentration (7).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated Ca 2ϩ activates calcium-activated proteases, calpains, which partially degrade myofibrillar proteins and ryanodine receptors, leading to breakdown of myofibrils and enhanced calcium efflux (11,27,31). Calcium-activated protease activity increases in atrophying soleus muscles during HSU (12,33) and spaceflight (28) and directly parallels the development of CCLs in tenotomy (5). Immobilized soleus muscles show significant increases in total calcium concentration (7).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most affected is the neuromuscular system. Weightlessness induces atrophy of skeletal muscle (Riley et al, 1987;Widrick et al, 1999) and cardiovascular deconditioning (Philpott et al, 1990;Antonutto and Prampero, 2003). Weightlessness also reduces functional capacity in limb skeletal muscle of animals including humans (Ilyina-Kakueva et al, 1976;Widrick et al, 1999;Fitts et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Weightlessness also reduces functional capacity in limb skeletal muscle of animals including humans (Ilyina-Kakueva et al, 1976;Widrick et al, 1999;Fitts et al, 2000). In vertebrate skeletal muscle, the greatest changes are observed in the limb antigravity muscles, such as soleus (Riley et al, 1987;Widrick et al, 1999;Harrison et al, 2003). Major changes in these muscles alter the expression of muscle protein isoforms, mainly myosin heavy chains (MHCs).…”
Section: Introductionmentioning
confidence: 99%
“…Some observations on fibers of young adult rats following 14 d of spaceflight suggest that subsarcolemmal mitochondria may be preferentially altered [47,69,70]. Bell et al [69] have shown that the relative loss of SDH activity in the subsarcolemmal vs. intermyofibril region following spaceflight is fiber-type dependent.…”
mentioning
confidence: 99%